NONLINEAR MODELS OF JUSTIFICATION OF DEVELOPMENT AND DESIGN OF WEAPONS AND MILITARY EQUIPMENT SYSTEMS - Тетерятник, В. Д. (Proceedings of National Aviation University (archive), 2021)
A mathematical model of the optimal distribution of reliability between the elements of complex weapons systems and military equipment during their creation according to the criterion of projected system operating costs is proposed.